Socioeconomic and Ecological Dimension of Certified and Conventional Arabica Coffee Production in North Sumatra, Indonesia - Saragih , Jef Rudiantho (Asian Journal of Agriculture and Rural Development, 2013)
The study was conducted in six subdistricts of Simalungun district, North Sumatra, Indonesia. The research objective is knowing the influence of socioeconomic and ecological factors on production of specialty Arabica coffee. Determination of the households sample was using Probability Proportional to Size and Simple Random Sampling for 79 units certified coffee farms and 210 units conventional coffee farms. Farmer’s data was analyzed with multiple linear regression model. Benefit of coffee certification compared to conventional coffee was analyzed by independen t-test. Increased production of arabica coffee could be achieved by intensification strategy through: increased application of suitable fertilizer recommendations, facilitation of coffee farm credit, optimization of land use (intercropping or multistrata coffee), optimization of family labour used, and application of GAPs (shade tree, organic fertilizer, coffee pruning, land conservation, and control of CBB). Ecological dimensions have important role in the development of specialty arabica coffee in the Simalungun highland; i.e. enhance productivity, improve coffee quality and support sustainability of coffee production. Productivity of certified arabica coffee is lower (8%) than conventional coffee, meanwhile premium price of certified coffee is only slightly higher (3.57%) than conventional coffee.